Limit charge bearing capacity testing method, characterization method and device

By testing the ultimate load-bearing capacity of the material at different current or voltage increases rates, the problem of ignoring the impact of upcurrent or voltage increases rates in the prior art is solved, and more accurate material performance evaluation is achieved, providing higher referenceable test results for material application design.

CN119667390AActive Publication Date: 2025-03-21SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311211584.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

When testing the ultimate bearing capacity of a material, the prior art ignores the impact of different upstream or voltage increase rates on the material, resulting in the mismatch of the test results with the actual application and reducing the referenceability of the test results.

Method used

By applying a test current or voltage to the test material at different preset current or voltage rise rates until the material blows, the ultimate load current or voltage at multiple rise rates is obtained and the correlation is analyzed to evaluate the material's ultimate charge carrying capacity.

Benefits of technology

This method can reflect the difference in the ultimate bearing capacity of the material at different upstream or voltage increase rates, provide higher reference test results, fill the gaps in the prior art, and provide more accurate guidance for the application design of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119667390A_ABST
    Figure CN119667390A_ABST
Patent Text Reader

Abstract

The invention discloses a test method, a characterization method and a device for the limit charge bearing capacity of a material. The test method comprises the following steps: applying test current or voltage to a to-be-tested material, and gradually increasing at a preset current rise rate or a preset voltage rise rate until the material is fused; acquiring limit bearing current or voltage at a plurality of different rates; based on the correlation, the limit charge carrying capacity is analyzed. The invention provides a test or characterization method for evaluating the ultimate bearing capacity of the material at different rising current or voltage rising rates for the first time, the obtained material test result can embody the difference of the ultimate bearing capacity at different rates, the blank in the field is filled, and the method has a wide application prospect. A test result with higher reference is provided for application design; a correlation characterization means for utilizing the ultimate bearing capacity and the inherent characteristics of the material under different rising current or voltage rising rates is provided for the first time, and the method belongs to a rapid and effective method for characterizing the inherent characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material characterization testing, and in particular to a testing method, a characterization method and a device for limiting charge carrying capacity. Background Art

[0002] The development of materials provides a material basis for the development of science and technology. At the same time, the development of science and technology also puts forward higher requirements on the performance of materials. How to accurately and effectively test and evaluate the performance of materials in simulated or real application scenarios is particularly important for the practical application guidance and further research and development of materials.

[0003] Moreover, as the size of devices in existing applications decreases and weapons and equipment become more high-performance and lightweight, the size of the conductive lines that power them needs to be reduced in the same proportion. The current density that the lines need to withstand will increase significantly, which also greatly increases the requirements for the material's ultimate current or voltage carrying capacity.

[0004] Therefore, accurately reflecting the ultimate bearing capacity of materials under different circumstances is crucial for the application design of materials. The existing technology provides some test methods for changing the test environment to test the bearing capacity of materials under different temperatures, pressures or atmospheres, but they all ignore the influence of different current rise or voltage rise rates on the ultimate bearing capacity of materials. In practical applications, the actual current rise or voltage rise rate faced by the material is often different from that during the test, which also leads to a mismatch between the test and the actual application, reducing the reference value of the test results.

[0005] In addition, the influence of different current or voltage increase rates on the ultimate load-bearing capacity of the material can further reflect some inherent properties of the material. The existing technology has ignored this phenomenon and missed a rapid and effective method to characterize the inherent properties of the material. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a testing method, a characterization method and a device for limiting charge carrying capacity.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] In a first aspect, the present invention provides a method for testing the limiting charge carrying capacity of a material, comprising:

[0009] Applying a test current or a test voltage to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted;

[0010] Obtaining the limiting load current or limiting load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates;

[0011] Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the limit charge carrying capacity of the material to be tested is analyzed.

[0012] In a second aspect, the present invention further provides a method for characterizing material properties, comprising:

[0013] Applying a test current or a test voltage to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted;

[0014] Obtaining the limiting load current or limiting load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates;

[0015] Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the characteristics of the material to be tested are analyzed.

[0016] In a third aspect, the present invention further provides a testing device for the limiting charge carrying capacity of a material, comprising:

[0017] A test chamber, used to provide a test environment, wherein at least one set of electrodes is disposed in the chamber, and the electrodes are used to be electrically connected to the material to be tested;

[0018] a programmable power supply, electrically connected to the electrodes, and at least used to apply a test current or voltage to the material to be tested;

[0019] The detection unit is at least used to monitor the macroscopic morphology and / or temperature change of the material to be tested in the test environment.

[0020] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:

[0021] The technical solution provided by the present invention proposes for the first time a test or characterization method for evaluating the ultimate charge carrying capacity of a material at different current or voltage increase rates. The obtained material test results can reflect the difference in the ultimate charge carrying capacity of the test material at different current or voltage increase rates, filling the gap in this field and providing test results with higher reference for the application design of the material.

[0022] For the first time, a characterization method that uses the correlation between the material's ultimate load-bearing capacity and the material's inherent properties at different current or voltage increase rates was proposed. This is a rapid and effective method for characterizing the material's inherent properties, and also fills a gap in this field.

[0023] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a structural schematic diagram of a test device provided by a typical implementation case of the present invention;

[0025] Figure 2 It is a schematic diagram of the interface of a test system provided by a typical implementation case of the present invention;

[0026] Explanation of the accompanying reference numerals: 1. Cavity; 2. Exhaust valve; 3. Infrared thermometer; 4. Wiring terminal; 5. Gas input valve; 6. High-speed camera; 7. Vacuum valve; 8. Water-cooling cable; 9. Programming power supply; 10. Terminal block. DETAILED DESCRIPTION

[0027] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0029] Moreover, relational terms such as “first” and “second” are merely used to distinguish one component or method step from another with the same name, but do not necessarily require or imply any such actual relationship or order between these components or method steps.

[0030] In order to fill the gap in existing testing and characterization methods, the purpose of the present invention is to propose a testing device and testing method for the limiting current carrying capacity of a material. By interconnecting the testing software with a programmable power supply, the test current or voltage increase speed can be output on demand, and the material current carrying capacity analysis and evaluation can be performed under different application environments simulated by the testing device.

[0031] To achieve the above object, one aspect of an embodiment of the present invention provides a method for testing the limiting charge carrying capacity of a material, which comprises the following steps:

[0032] A test current or a test voltage is applied to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted.

[0033] Obtain the limit load current or limit load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates.

[0034] Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the limit charge carrying capacity of the material to be tested is analyzed.

[0035] Based on the above technical scheme, the present invention is first based on the law discovered by the inventor, that is, under different current increase rates or voltage increase rates, the ultimate bearing capacity of the material itself is not constant, but changes very regularly and obviously with the change of the current increase rate or voltage increase rate. Its ultimate bearing capacity may differ by several times under different current increase or voltage increase rates. This difference can easily lead to the inability of existing testing methods to accurately reflect how much current / voltage the material can withstand in a specific application scenario; and the above technical scheme utilizes the phenomena and laws discovered by the present invention, and through multi-point testing, objectively reflects the influence of different current increase or voltage increase rates on the ultimate bearing capacity. For example, a standard curve of rate-bearing capacity can be provided. In specific application design, the designer can refer to the curve and the current increase rate that the material is subjected to in the target application scenario to accurately define the design limit, providing a very reference test result.

[0036] In some embodiments, when the preset current increase rate is lower than a first threshold and / or the preset voltage increase rate is lower than a second threshold, the limiting load-bearing current is positively correlated with the preset current increase rate, and / or the limiting load-bearing voltage is positively correlated with the preset voltage increase rate.

[0037] When the preset current increase rate is above a first threshold and / or the preset voltage increase rate is above a second threshold, the limit load current is negatively correlated with the preset current increase rate, and / or the limit load voltage is negatively correlated with the preset voltage increase rate.

[0038] In some embodiments, the testing method further comprises: recording the maximum temperature at which the material to be tested melts.

[0039] In some embodiments, the material to be tested is tested under selected environmental conditions, which include any one or a combination of two or more of protective atmosphere, vacuum, oxidizing atmosphere, reducing atmosphere, humidity, and ambient temperature.

[0040] In some embodiments, the limiting charge carrying capacity includes a current increase rate corresponding to the first threshold, and / or a voltage increase rate corresponding to the second threshold.

[0041] In some embodiments, the limiting charge carrying capacity further includes a limiting carrying current value corresponding to the first threshold value, and / or a limiting carrying voltage value corresponding to the second threshold value.

[0042] As some typical application examples of the above technical solutions, a specific experimental case of the present invention is, for example: using Figure 1 The experimental setup and Figure 2 In the test system shown, input the starting current and ending current of the test, and set the current rise speed or voltage rise speed. For example, set the voltage rise speed to 100V / s, 400V / s, 800V / s, 1200V / s, and 1600V / s in sequence to test the material's limiting current carrying capacity at different voltage rise speeds. As the test proceeds, the system will automatically record the material's limiting current carrying value, limiting voltage carrying value, the highest temperature when the material melts, and the duration of the material being energized, and draw related I / T, I / V, I / t, V / T and other relationship curves. Researchers can conduct follow-up work based on comprehensive evaluations such as relationship diagrams, test data, and macroscopic morphology.

[0043] A second aspect of an embodiment of the present invention further provides a method for characterizing material properties, which includes:

[0044] A test current or a test voltage is applied to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted.

[0045] Obtain the limit load current or limit load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates.

[0046] Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the characteristics of the material to be tested are analyzed.

[0047] In some embodiments, the intrinsic properties include any one or a combination of defect density, crystallinity, and micro-orientation of the material to be tested.

[0048] The inventors of the present invention have also discovered the correlation between the above-mentioned correlation and the inherent properties of the material in long-term practice. For the same material, such as carbon fiber, when its internal microstructure is different, such as different crystallinity or orientation, it will also cause the relationship curve between the ultimate bearing capacity and the rate of increase of current or voltage of the same carbon fiber material to change. By using this law, a variety of technical means can be developed to use the above-mentioned phenomenon to qualitatively or even quantitatively characterize the inherent properties of the material.

[0049] For example, in some embodiments, the characterization method may include:

[0050] Through multiple correlation curves of the preset current increase rate or the preset voltage increase rate and the limit load current or the limit load voltage, the first threshold corresponding to the inflection point of the limit load current and / or the second threshold corresponding to the inflection point of the limit load voltage are obtained.

[0051] The defect density is negatively correlated with the first threshold and / or the second threshold; and / or, the degree of crystallization is positively correlated with the first threshold and / or the second threshold; and / or, the micro-orientation is positively correlated with the first threshold and / or the second threshold.

[0052] In some embodiments, the characterization method may further include: obtaining a maximum limit load current value or a maximum limit load voltage value through the correlation curve.

[0053] The defect density is negatively correlated with the maximum limit load-bearing current value and / or the maximum limit load-bearing voltage value; and / or the degree of crystallization is positively correlated with the maximum limit load-bearing current value and / or the maximum limit load-bearing voltage value; and / or the micro-orientation is positively correlated with the maximum limit load-bearing current value and / or the maximum limit load-bearing voltage value.

[0054] See also Figure 1 and Figure 2 The embodiment of the present invention further provides a testing device for the limiting charge carrying capacity of a material, which comprises:

[0055] The cavity 1 is used to accommodate the material to be tested. At least one group of electrodes is arranged in the cavity 1, and the electrodes can be electrically connected to the material to be tested.

[0056] A programmable power supply is electrically connected to the electrodes and is used to apply a controllable current and / or voltage.

[0057] And an observation unit is arranged on the cavity 1 and is used to observe the macroscopic morphology and / or temperature change of the material to be tested.

[0058] As some typical application examples of the above technical solution, the main body of the testing device includes a testing chamber 1, a programmable power supply, and auxiliary equipment parts.

[0059] in:

[0060] Cavity 1: It can realize test environments such as vacuum and protective gas atmosphere, and is used to evaluate the current-carrying performance of materials under different environmental atmospheres.

[0061] Programmable power supply part: Through the interconnection between the software and the programmable power supply, the setting of different current increase speeds or voltage increase speeds can be realized, and the evaluation of the current flow capacity of the evaluation material at different current increase or voltage increase speeds can be carried out.

[0062] Auxiliary equipment part: mainly includes infrared temperature measuring equipment, which is used to record the temperature change of the material during the test; high-speed camera equipment, which is used to record the macroscopic morphological changes of the material during the test; and chiller equipment, which is used to provide cooling circulating water to assist in the temperature reduction protection of the test connection cables and the terminal 10.

[0063] In some embodiments, the cavity 1 is a closed structure, and a gas passage is provided on the cavity wall, and the gas passage is used to transport gas into the cavity 1 or to draw a vacuum.

[0064] In some embodiments, the electrodes are provided in multiple groups.

[0065] In some embodiments, multiple groups of electrodes are arranged sequentially along a specified direction.

[0066] In some embodiments, the device may further include a water cooling unit, which is connected to the electrode and the cable between the electrode and the programming power supply 9 through a cooling pipeline to cool the electrode and the cable.

[0067] As a typical application example of the above technical solution, a specific testing device such as Figure 1 As shown, it includes the main part of the test chamber 1 of the equipment; an exhaust valve 2, which is arranged on the wall of the chamber 1 and is used to release the air and break the vacuum of the chamber 1; an infrared thermometer 3, which is arranged on the chamber 1, and tests and records the real-time temperature of the material during the current-carrying test; a material current-carrying test sample terminal 4, which is equivalent to an electrode, is arranged in the chamber 1 and is used to make electrical contact with the material to be tested; a gas input valve 5, which is arranged on the wall of the chamber 1, and can selectively input nitrogen, argon or other protective gases into the test chamber 1 to achieve the relevant environmental test atmosphere; a high-speed camera 6, which is arranged on the chamber 1 and is used to record the macroscopic morphological changes of the material during the test; a vacuum valve 7, which is arranged on the wall of the chamber 1 and is externally connected to a mechanical pump and a molecular pump, and the final vacuum degree is ≤9.0×10 -5Pa, the exhaust valve 2, the vacuum valve 7 and the gas input valve 5 together constitute a gas passage; the water-cooling cable 8 connects the terminal 10 on the test chamber 1 with the programming power supply 9, which is used to supply power to the test material; the programming power supply 9, through the interconnection with the control software, can realize the test of the power supply current according to the set voltage increase speed or current increase speed, and evaluate the material's limiting current carrying capacity under different voltage or current increase speeds; the material current carrying test terminal 10, electrically connected to the terminal 4 and the water-cooling cable 8, this terminal 10 can be set in multiple groups in the test chamber 1, so as to carry out multiple groups of comparative experiments at the same time.

[0068] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0069] Example 1

[0070] This embodiment illustrates a test process of the limit charge carrying capacity of a carbon nanotube fiber, which is specifically as follows:

[0071] Using carbon nanotube fibers as the test material, the starting current is set to 0A, and the ending current is set to the upper limit of the power supply output. The material's limiting current carrying capacity is tested at different current rising speeds. The test results are shown in the following table:

[0072]

[0073] It can be concluded from the test data that the same sample exhibits different limiting current carrying capacities at different current rising speeds, with the maximum and minimum being able to differ by nearly 5 times. Combined with other performance parameters recorded by the test system, this will help guide further research.

[0074] Specifically, it can be seen that as the current rise rate increases, the limiting current-carrying value will first rise and then fall. The threshold corresponding to the middle inflection point and the maximum current-carrying value are important comprehensive indicators that comprehensively reflect the material's carrying capacity.

[0075] For example, when designing the application of this material, if the application is faced with a current increase rate of 100-500A / s, the current should be limited to less than 3A. If the application is faced with a current increase rate of 1300-1700A / s, the maximum current limit should be increased to 8A.

[0076] Alternatively, when designing the device, the current increase rate of the carbon nanotube conductor is controlled to be between 1300-1700A / s as much as possible, so as to obtain the best overcurrent resistance.

[0077] Example 2

[0078] This embodiment illustrates a carbon nanotube fiber orientation characterization process, which is specifically as follows:

[0079] In the preparation process of carbon nanotube fibers, carbon nanotube fibers with various orientation degrees are obtained by controlling the stretching rate. The same test method as in Example 1 is used to test and it is found that the curve inflection point current increase rate and the maximum current carrying value corresponding to the carbon nanotube fibers with different orientation degrees are different.

[0080] The basic rule is: at the corresponding current increase rate, the better the orientation, the greater the maximum current carrying value.

[0081] Therefore, this embodiment establishes a method for characterizing the orientation degree of carbon nanotube fibers. Without relying on polarized Raman spectroscopy, the orientation degree of the carbon nanotube fibers can be reflected to a certain extent simply by testing the change in the limiting current carrying value at different current increase rates.

[0082] Example 3

[0083] This embodiment illustrates a test process of the limit charge carrying capacity of carbon fiber, which is specifically as follows:

[0084] Use 1k carbon fiber as the test material, set the starting current to 0A, and the ending current to the upper limit of the power supply output. Test the material's limiting current carrying capacity at different current rising speeds. The test results are shown in the following table:

[0085]

[0086]

[0087] Example 4

[0088] This embodiment illustrates a process of characterizing the crystallinity of a carbon nanotube fiber, which is specifically as follows:

[0089] In the preparation process of carbon nanotube fibers, different fibers will show good or bad performance due to the influence of various parameters. How to quickly and effectively judge the performance of the fibers and guide the confirmation and production of process parameters is particularly important. Through the same test method as in Example 1, it is found that the maximum current carrying values ​​of carbon nanotube fibers with different crystallinity at the corresponding current increase rate are different.

[0090] The basic rule is: at the corresponding current increase rate, the better the crystallinity, the greater the maximum current carrying value. This method can quickly and effectively determine the quality of the material's crystallinity, avoiding too many cumbersome and expensive tests, such as XRD tests, etc., filling the gap in the rapid and low-cost crystallinity test of carbon nanotube fibers.

[0091] Based on the above embodiments, it can be clearly seen that the technical solution provided in the embodiments of the present invention proposes for the first time a test or characterization method for evaluating the ultimate charge carrying capacity of a material at different current rise or voltage rise rates. The obtained material test results can reflect the difference in the ultimate charge carrying capacity of the test material at different current rise or voltage rise rates, filling the gap in this field and providing a test result with higher reference for the application design of the material.

[0092] The embodiment of the present invention proposes for the first time a means of characterizing the correlation between the ultimate load-bearing capacity of a material and the inherent properties of the material at different current or voltage increase rates, which is a rapid and effective method for characterizing the inherent properties of a material and fills a gap in this field.

[0093] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for testing the limiting charge carrying capacity of a material, characterized in that: include: Applying a test current or a test voltage to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted; Obtaining the limiting load current or limiting load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates; Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the limit charge carrying capacity of the material to be tested is analyzed.

2. The testing method according to claim 1, characterized in that: When the preset current increase rate is lower than a first threshold value and / or the preset voltage increase rate is lower than a second threshold value, the limit load current is positively correlated with the preset current increase rate, and / or the limit load voltage is positively correlated with the preset voltage increase rate; When the preset current increase rate is above a first threshold value and / or the preset voltage increase rate is above a second threshold value, the limit load current is negatively correlated with the preset current increase rate, and / or the limit load voltage is negatively correlated with the preset voltage increase rate; Preferably, it also includes: recording the highest temperature when the material to be tested is melted; Preferably, the material to be tested is tested under selected environmental conditions, and the selected environmental conditions include any one or a combination of two or more of protective atmosphere, vacuum, oxidizing atmosphere, reducing atmosphere, humidity, and ambient temperature.

3. The testing method according to claim 2, characterized in that: The limit charge carrying capacity includes a current increase rate corresponding to the first threshold value, and / or a voltage increase rate corresponding to the second threshold value; Preferably, the limit charge carrying capacity also includes a limit carrying current value corresponding to the first threshold value, and / or a limit carrying voltage value corresponding to the second threshold value.

4. A method for characterizing material properties, characterized in that: include: Applying a test current or a test voltage to the material to be tested, wherein the test current gradually increases at a preset current increase rate, and the test voltage gradually increases at a preset voltage increase rate, until the material to be tested is melted; Obtaining the limiting load current or limiting load voltage of the material to be tested corresponding to a plurality of different preset current increase rates or preset voltage increase rates; Based on the correlation between the plurality of preset current increase rates or the preset voltage increase rates and the limit load current or the limit load voltage, the characteristics of the material to be tested are analyzed.

5. The characterization method according to claim 4, characterized in that: The material properties include any one or a combination of the crystallinity and microscopic orientation of the material to be tested.

6. The characterization method according to claim 5, characterized in that Specifically include: Obtaining, through a plurality of correlation curves between the preset current increase rate or the preset voltage increase rate and the limit load current or the limit load voltage, a first threshold corresponding to an inflection point of the limit load current and / or a second threshold corresponding to an inflection point of the limit load voltage; The degree of crystallization is positively correlated with the first threshold and / or the second threshold; And / or, the microscopic orientation is positively correlated with the first threshold and / or the second threshold.

7. The characterization method according to claim 6, characterized in that: Also includes: Obtaining the maximum limit load current value or the maximum limit load voltage value through the relevant curve; The degree of crystallization is positively correlated with the maximum limit load-bearing current value and / or the maximum limit load-bearing voltage value; and / or, the microscopic orientation is positively correlated with the maximum limit load-bearing current value and / or the maximum limit load-bearing voltage value.

8. A device for testing the limiting charge carrying capacity of a material, characterized in that: include: A test chamber, used to provide a test environment, wherein at least one set of electrodes is disposed in the chamber, and the electrodes are used to be electrically connected to the material to be tested; a programmable power supply, electrically connected to the electrodes, and at least used to apply a test current or voltage to the material to be tested; The detection unit is at least used to monitor the macroscopic morphology and / or temperature change of the material to be tested in the test environment.

9. The testing device according to claim 8, characterized in that: The test cavity is a closed structure, and a gas passage is also provided on the cavity wall, and the gas passage is at least used to transport gas into the cavity or to evacuate the cavity to change the test environment; Preferably, the electrodes are provided in multiple groups; Preferably, the plurality of groups of electrodes are arranged sequentially along a specified direction.

10. The testing device according to claim 8, characterized in that: It also includes a water cooling unit, which is connected to the electrode and the cable between the electrode and the programming power supply through a cooling pipeline, and is used to cool the electrode and the cable.

Citation Information

Patent Citations

  • Mechanical performance testing system and method for carbon nanotube fibers in high-temperature state

    CN108387458A

  • Insulating material aging state evaluation method based on linear boost and isothermal relaxation current

    CN113777138A

  • Method and device for rapidly testing fusing characteristics of meltof filament fuse

    CN113985323A

  • Capacitive load insulation detection method, device and equipment

    CN115792522A

  • Photoelectric test system for electrochromic functional film

    CN116337784A